Analyzing Social Networks: Unveiling the Dynamics within the Honduran Entrepreneurial Ecosystem - ACEVEDO AMAYA, MARIO ROBERTO; ORTEGA-JIMENEZ, CESAR H.; FLORES JUANEZ, KARLA MARIA (LACCEI, 2024)
This research addresses the prevailing gaps in our understanding of the entrepreneurial landscape in Honduras through the application of the Social Network Analysis (ARS) method, coupled with statistical mediation and multiple regression techniques. Our study delves into the intricate business ecosystem of Honduras, emphasizing the interactions among key stakeholders, including the government, private sector, academia, non-governmental organizations, and support agencies. Employing social network analysis, we scrutinize the network’s structure, density, reciprocity, and the intensity of connections between these pivotal actors. Statistical mediation and multiple regression models are harnessed to investigate the mediating effects of these actor connections on the intricate relationship between influence and the diffusion of business activities. Our findings uncover a bimodal nature within the entrepreneurial ecosystem of Honduras, marked by constraints in both social and material attributes. The ecosystem exhibits low-density bidirectional relationships, limited reciprocity, and constrained actor connections. The analysis further highlights that the level of connection among actors partially mediates the influence on the diffusion of business activities.